2021
DOI: 10.3389/fvets.2021.670645
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Fecal Bacterial Microbiota of Wintering Whooper Swans (Cygnus Cygnus)

Abstract: There are many and diverse intestinal microbiota, and they are closely related to various physiological functions of the body. They directly participate in the host's food digestion, nutrient absorption, energy metabolism, immune response, and many other physiological activities and are also related to the occurrence of many diseases. The intestinal microbiota are extremely important for maintaining normal physical health. In order to explore the composition and differences of the intestinal microbiota of whoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 51 publications
7
7
0
Order By: Relevance
“…The average proportion of bacteria from these three phyla in the sequenced data reached 98.56%. The dominant bacterial phyla identified in the current study were consistent with those identified by Wang et al ( 21 ) in wintering whooper swans of Sanmenxia in Henan province and Rongcheng in Shandong province and those identified by Wang et al ( 11 ) in wintering black-necked cranes ( 11 ). Therefore, bacteria from these three phyla are dominant in most wild birds analyzed to date.…”
Section: Discussionsupporting
confidence: 90%
“…The average proportion of bacteria from these three phyla in the sequenced data reached 98.56%. The dominant bacterial phyla identified in the current study were consistent with those identified by Wang et al ( 21 ) in wintering whooper swans of Sanmenxia in Henan province and Rongcheng in Shandong province and those identified by Wang et al ( 11 ) in wintering black-necked cranes ( 11 ). Therefore, bacteria from these three phyla are dominant in most wild birds analyzed to date.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the gut microbiota of three wild bird species were found to mainly comprise six phyla, including Firmicutes, Proteobacteria, Fusobacteria, Actinobacteria, Bacteroidetes, and Campilobacterota, consistent with studies on other birds, such as the Greylag Geese ( Anser anser ; Wang et al, 2018 ), Bengalese Finch ( Lonchura striata domestica ) and Zebra Finch ( Taeniopygia guttata ; Maraci et al, 2021 ), Hooded Crane ( Grus monacha ; Fu et al, 2020 ), and Whooper Swan ( Cygnus cygnus ; Wang et al, 2021 ). Firmicutes, the most dominant species among the three hosts, generally dominate the gut microbiota in all animals and play an important role in maintaining gut homeostasis and assisting digestion.…”
Section: Discussionsupporting
confidence: 89%
“…Firmicutes and Proteobacteria were the most abundant microbiota in the relict gulls at both sites. This is consistent with the results of previous studies on other avian species ( 27 , 33 ). These phyla exist in multiple avian species, indicating that they are important functional bacteria in the gastrointestinal tract of relict gulls.…”
Section: Discussionsupporting
confidence: 94%
“…DNA was extracted using the E.Z.N.A. Stool DNA Kit (D4015, Omega, Inc., GA, USA), according to the manufacturer's instructions, as described ( 27 ). Generally, total DNA was isolated and eluted in elution buffer and used for polymerase chain reaction (PCR), the amplified region was the V3–V4 hypervariable region of the bacterial 16S rRNA gene, the used primers were 341F (5′-CCTACGGGNGGCWGCAG-3′) and 805R (5′-GACTACHVGGGTATCTAATCC-3′).…”
Section: Methodsmentioning
confidence: 99%